Kant on Moral Agency: Beyond the Incorporation Thesis - Viljanen Valtteri (Kant-Studien, 2022)
This paper aims to discern the limits of the highly influential Incorporation Thesis to give proper weight to our sensuous side in Kant’s theory of moral action. I first examine the view of the faculties underpinning the theory, which allows me to outline the passage from natural to rational action. This enables me to designate the factors involved in actual human agency and thereby to show that, contrary to what the Incorporation Thesis may tempt one to believe, we do not always act on maxims. The result is a revised and more balanced view of how Kant sees the character of moral life.